En fallstudie av muntlig kommunikation inom matematikundervisning i gymnasieskolan - Hatami,Nawid; Öster,Adrian (Master’s Theses in Mathematical Sciences, 2025)
This paper aims to analyse the oral communication patterns amongst upper secondary school students within the subject of math. To this end, Mohan’s Knowledge Framework (1986) has been utilised, which seeks to sort knowledge into six different categories: three practical and three theoretical. The data collection consisted of observations made from lessons where the students solved math problems in groups, followed by stimulated recall interviews. The results suggest that students mainly tend to use practical language and that they also showcase similar language in the interviews but also highlight certain settings, such as presenting a problem in front of the whole class, where they communicate using more of the theoretical aspects of the Knowledge Framework. These findings provide insight for teachers who are looking to implement more oral mathematics in their lessons and how to possibly bring about more rich and theoretical discussions within student groups.
Keywords: Math Education; Secondary Education; Communication in Mathematics; Oral Mathematics; Group Discussions